ANALYSIS OF THE RIGHT STRATEGY FOR ADAPTING TRADITIONAL RETAIL BUSINESS IN THE DIGITAL ERA: A CASE STUDY OF BU YUNI'S SNACK SHOP USING THE BUSINESS MODEL CANVAS APPROACH: Array - Sulis Setiawati; Siti Amelia Novita Sari (JABI (Journal of Accounting and Business Issues), 2025)
The traditional retail industry, especially Indonesia's small local stores (warung), has been greatly disrupted by the quick development of digital technology. In order to stay competitive in the digital age, this study is to assess Warung Jajan Bu Yuni's current business model using the Business Model Canvas (BMC) framework and determine suitable adaptation methods. In-depth interviews with the owner were used to gather data for a single case study using a qualitative descriptive approach. The results show that the company continues to run conventionally, without the use of digital technologies, depending on direct sales and personal connections with local clients. To adapt to shifting consumer behavior, a number of crucial BMC components—including channels, customer connections, value propositions, income sources, and partnerships—need to be modified. The suggested adaptation tactics include partnering with local communities, providing basic delivery services, and promoting using WhatsApp Stories. Traditional retailers can become part of the digital ecosystem without losing their social and cultural identity thanks to these gradual and context-based adjustments